Rural tourism and sustainable development in the district of General Pueyrredon (Argentina). Challenges and opportunities in the context of touristification - Benseny, Graciela (2024)
The district of General Pueyrredon (Argentina), with Mar del Plata as its main city, has a large peri-urban territory with scenic, agricultural and cultural characteristics that favour rural tourism, based on local cultural traditions and contact with nature. In recent decades, it has become a strategy for economic diversification that favours sustainable development and careful management of the effects of touristification, which can lead to the commodification of culture and the loss of local identity. The aim is to explore the opportunities and challenges of rural tourism in the district of General Pueyrredon, analysing its relationship with sustainable development and the implications of touristification in the region. An exploratory and descriptive study is carried out, consulting bibliographic, documentary, graphic and virtual sources, taking as a case the Estancia Santa Isabel, whose productive diversification allows its positioning as an innovative reference of rural tourism.